186Os–187Os and highly siderophile element abundance systematics of the mantle revealed by abyssal peridotites and Os-rich alloys. (1st March 2017) - Day, James M.D.; Walker, Richard J.; Warren, Jessica M.
Abstract: Abyssal peridotites are oceanic mantle fragments that were recently processed through ridges and represent residues of both modern and ancient melting. To constrain the nature and timing of melt depletion processes, and the composition of the mantle, we report high-precision Os isotope data for abyssal peridotites from three ocean basins, as well as for Os-rich alloys, primarily from Mesozoic ophiolites. These data are complemented by whole-rock highly siderophile element (HSE: Os, Ir, Ru, Pt, Pd, Re), trace- and major-element abundances for the abyssal peridotites, which are from the Southwest Indian (SWIR), Central Indian (CIR), Mid-Atlantic (MAR) and Gakkel Ridges. The results reveal a limited role for melt refertilization or secondary alteration processes in modifying abyssal peridotite HSE compositions. The abyssal peridotites examined have experienced variable melt depletion (2% to >16%), which occurred >0.5 Ga ago for some samples. Abyssal peridotites typically exhibit low Pd/Ir and, combined with high-degrees of estimated total melt extraction, imply that they were relatively refractory residues prior to incorporation into their present ridge setting. Recent partial melting processes and mid-ocean ridge basalt (MORB) generation therefore played a limited role in the chemical evolution of their precursor mantle domains. The results confirm that many abyssal peridotites are not simple residues of recent MORB source melting, having a more complex and long-lived depletion history. Peridotites from the Gakkel Ridge, SWIR, CIR and MAR indicate that the depleted MORB mantle has 186 Os/ 188 Os of 0.1198356 ± 21 (2SD). The Phanerozoic Os-rich alloys yield an average 186 Os/ 188 Os within uncertainty of abyssal peridotites (0.1198361 ± 20). Melt depletion trends defined between Os isotopes and melt extraction indices (e.g., Al2 O3 ) allow an estimate of the primitive mantle (PM) composition, using only abyssal peridotites. This yields 187 Os/ 188 Os (0.1292 ± 25), and 186 Os/ 188 Os of 0.1198388 ± 29, both of which are within uncertainty of previous primitive mantle estimates. The 186 Os/ 188 Os composition of the PM is less radiogenic than for some plume-related lavas, with the latter requiring sources with high long-term time-integrated Pt/Os. Estimates of primitive mantle HSE concentrations using abyssal peridotites define chondritic Pd/Ir, which differs from previous supra-chondritic estimates for Pd/Ir based on peridotites from a range of tectonic settings. By contrast, estimates of PM yield supra-chondritic Ru/Ir. The cause of enhanced Ru in the mantle remains enigmatic, but may reflect variable partitioning behavior of Ru at high pressure and temperature.